Costimulatory Function of Cd58/Cd2 Interaction in Adaptive Humoral Immunity in a Zebrafish Model - Shao, Tong; Shi, Wei; Zheng, Jia-yu; Xu, Xiao-xiao; Lin, Ai-fu; Xiang, Li-xin; Shao, Jian-zhong (Frontiers in Immunology, 2018)
CD58 and CD2 have long been known as a pair of reciprocal adhesion molecules involved in the immune modulations of CD8+ T and NK-mediated cellular immunity in humans and several other mammals. However, the functional roles of CD58 and CD2 in CD4+ T-mediated adaptive humoral immunity remain poorly defined. Moreover, the current functional observations of CD58 and CD2 were mainly acquired from in vitro assays, and in vivo investigation is greatly limited due to the absence of a Cd58 homology in murine models. In the present study, we identified cd58 and cd2 homologs from the model species zebrafish (Danio rerio). These two molecules share conserved structural features to their mammalian counterparts. Functionally, cd58 and cd2 were significantly upregulated on antigen-presenting cells and Cd4+ T cells upon antigen stimulation. Blockade or knockdown of Cd58 and Cd2 dramatically impaired the activation of antigen-specific Cd4+ T and mIgM+ B cells, followed by the inhibition of antibody production and host defense against bacterial infections. These results indicate that CD58/CD2 interaction was required for the full activation of CD4+ T-mediated adaptive humoral immunity. The interaction of Cd58 with Cd2 was confirmed by co-immunoprecipitation and functional competitive assays by introducing a soluble Cd2 protein. This study highlights a new costimulatory mechanism underlying the regulatory network of adaptive immunity and makes zebrafish an attractive model organism for the investigation of CD58/CD2-mediated immunology and disorders. It also provides a cross-species understanding of the evolutionary history of costimulatory signals from fish to mammals as a whole.